2022
DOI: 10.2174/1381612827666210701150315
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology-based Approaches and Investigational Therapeutics against COVID-19

Abstract: : Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel coronavirus which is currently responsible for the global pandemic since December 2019. This class of coronavirus has affected 217 countries around the world. Most of the countries have taken some non-remedial preventive actions like country lockdown, work from home, travel bans, and the most significant one is social isolation. Pharmacists, doctors, nurses, technologists, and all other healthcare professionals are playing a pivotal role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 248 publications
0
8
0
Order By: Relevance
“…Several investigations have suggested that amyloid protein buildup triggers astrogliosis; nevertheless, activated astrocytes produce an A42-immunopositive substance that changes in concentration across the cerebral cortex in AD brains depending on the severity of the disease. Although the precise method by which A42 material collects inside active astrocytes is unknown, it is thought to be owing to either phagocytosis or endocytosis [194][195][196][197][198][199] (Figures 5 and 6).…”
Section: The Interaction Of Neurons and Glia In Alzheimer'smentioning
confidence: 99%
“…Several investigations have suggested that amyloid protein buildup triggers astrogliosis; nevertheless, activated astrocytes produce an A42-immunopositive substance that changes in concentration across the cerebral cortex in AD brains depending on the severity of the disease. Although the precise method by which A42 material collects inside active astrocytes is unknown, it is thought to be owing to either phagocytosis or endocytosis [194][195][196][197][198][199] (Figures 5 and 6).…”
Section: The Interaction Of Neurons and Glia In Alzheimer'smentioning
confidence: 99%
“…Sildenafil (Viagra), for example, is currently used to treat erectile dysfunction in men but was primarily designed for the treatment of angina [ 40 ]. Several medicines, including anticancer drugs, are yet to be discovered, as their associated target proteins (both primary and non-target) are unknown [ 7 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Furthermore, several therapeutic cancer targets remain “unchecked” by pharmaceutical establishments.…”
Section: Anticancer Drug Target Predictionmentioning
confidence: 99%
“…e methodological quality of eligible RCTs was evaluated independently through the Cochrane Handbook for Systematic Reviews of Interventions. Specifically, it includes (1) Selection bias: which describes in detail the method for generating randomly assigned sequences; (2) e implementation of bias: concealment of allocation; (3) Measurement bias: blinding of participants, personnel, and outcome assessors; (4) Follow-up of bias: incomplete data on outcome; (5) Reporting bias: selectively reporting favorable results and hiding unfavorable ones; (6) Other biases: conflict of interest, insufficient sample size, unbalanced baseline. Each entry was assessed as "low risk," "unclear risk," or "high risk" regarding this statement.…”
Section: Risk Of Bias Assessment According To the Cochranementioning
confidence: 99%
“…e remaining 3 studies lacked any description of the allocation hiding method, which was considered to have an unclear bias risk [26,28,36]. e following methods respectively concealed the 10 studies: (1) Randomized block design treatment assignment [24]; (2) the study personnel received a sealed opaque envelope with an assignment to intervention or control group [25]; (3) Use SAS software and interactive randomization tools in REDCap (Research Electronic Data Capture) [27,34]; (4) Random assignment was unstratified and done by local clinical or research staff using a web-based interface with allocation concealment [29]; (5) Treatment assignments were generated using randomly permuted blocks [30,31,33]; (6) e individual recruiting the patient (senior physician responsible for therapeutic intervention) contacted the center by phone after the patient is enrolled.…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
See 1 more Smart Citation